2005
DOI: 10.1016/j.ejheart.2004.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nurse-led, clinic and home-based intervention on recurrent hospital use in chronic heart failure

Abstract: Background: Few studies have examined the potential benefits of specialist nurse-led programs of care involving home and clinic-based follow-up to optimise the post-discharge management of chronic heart failure (CHF). Objective: To determine the effectiveness of a hybrid program of clinic plus home-based intervention (C+HBI) in reducing recurrent hospitalisation in CHF patients. Methods: CHF patients with evidence of left ventricular systolic dysfunction admitted to two hospitals in Northern England were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 38 publications
(47 reference statements)
3
82
0
1
Order By: Relevance
“…Similar programs offering home-based visits to patients with heart failure in collaboration with health professionals other than pharmacists, including nurse practitioners, have also been shown to be effective. 24,25 The white Paper on Pharmacy in England 26 identifies pharmacists as an underutilized resource in the health system, and the United Kingdom government is encouraging such role extension. 8 If the findings of this study are replicated in other patient groups who are at high risk of medication misadventure and consequent rehospitalization, there will be an even stronger case to require pharmacists to be involved in this extension of their role in collaboration with physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Similar programs offering home-based visits to patients with heart failure in collaboration with health professionals other than pharmacists, including nurse practitioners, have also been shown to be effective. 24,25 The white Paper on Pharmacy in England 26 identifies pharmacists as an underutilized resource in the health system, and the United Kingdom government is encouraging such role extension. 8 If the findings of this study are replicated in other patient groups who are at high risk of medication misadventure and consequent rehospitalization, there will be an even stronger case to require pharmacists to be involved in this extension of their role in collaboration with physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis showed a significant reduc- Reasons for exclusion: duplicates; editorials; letters; comments; reviews; protocols without data, without an intervention; not on transition, transition within hospitals, to nursing home, within specialist services; from emergency to the hospital; emergency conditions; education/health promotion; speci c intervention (eg, medication prescription only) 5 trials identied through the screening of reference lists 41 included in the systematic review * References 35,37,38,41,[44][45][46][47]50,54,55,57,60,67,68,73 T …”
Section: Effect On All-cause Hospital Readmissionmentioning
confidence: 99%
“…28 Later studies implementing team-based HF clinic interventions also reported improved functional status, quality of life, and HF medication optimization, and reduction in hospital readmissions, length of hospital stay, and health care costs. [29][30][31][32][33][34][35][36][37] Reduction in mortality and HF hospitalizations were further supported by subsequent meta-analyses evaluating HF clinic care in comparison with usual care. 28,[38][39][40] A systematic review of 29 randomized trials (5039 patients) incorporating multidisciplinary strategies for HF management reported reduced mortality, HF hospitalizations, and all-cause hospitalizations.…”
Section: Introductionmentioning
confidence: 98%